The effectiveness of psychological interventions for reducing PTSD and psychological distress in first responders: A systematic review and meta-analysis - Alshahrani, Khalid M.; Johnson, Judith; Prudenzi, Arianna; O’Connor, Daryl B. (PloS one, 2022)
First responders are faced with stressful and traumatic events in their work that may affect their psychological health. The current review examined the effectiveness of psychological interventions to treat posttraumatic stress disorder (PTSD), anxiety, depression, stress and burnout in first responders. Four databases were searched to identify controlled studies that examined the efficacy of psychological interventions to reduce PTSD symptoms (primary outcome) in first responders (including firefighters, police/law enforcement officers, search and rescue personnel, emergency and paramedics teams). Secondary outcomes were anxiety, depression, burnout, and stress. 15 studies were identified, including 10 studies that measured PTSD, 7 studies for anxiety, 10 studies for depression, 7 studies for stress and 1 for burnout. Interventions were associated with a significant reduction in PTSD (SDM = -0.86; 95% CI = -1.34 -- 0.39), depression (SDM = -0.63; 95% CI = -0.94 --0.32), and anxiety (SDM = -0.38; 95% CI = -0.71 --0.05) but not stress (SDM = -0.13; 95% CI = -0.51-0.25). CBT-based and clinician-delivered interventions were associated with significantly greater reductions in PTSD than other types of interventions and non-clinician interventions, but no differences were found for depression. There was evidence of moderate to high risk of bias across all studies. Psychological interventions are effective in reducing PTSD, depression and anxiety symptoms but not stress in first responders. Further research is needed using high quality randomised designs over longer periods of follow-up.